The Utilisation of A Heating Plate For Laboratory-Scale Fixation of Histology Specimens - Burhannudin, Burhannudin (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2025)
Background: The challenge of expediting the histology preparation process without compromising quality has led to exploring microwave technology. However, it is yet to be determined whether heating plates are effective. Investigating the potential of enhancing histology preparation processing is an area of interest. Methods: This experimental study utilised a post-test-only control group design approach using forty-five specimens of Wistar white rat (Rattus norvegicus) hepatic tissues, which were divided into nine hotplate treatment groups. The groups were exposed to temperatures of 60°C (H1), 70°C (H2), and 80°C (H3) for 3 minutes (T1), 5 minutes (T2), and 10 minutes (T3), respectively. The tissues were fixed using FineFix solution and processed for routine staining, following the methodology described in the previous study. The quality of the preparation was assessed by scoring the results of Haematoxylin-Eosin staining for each treatment. The scores were analysed using the Kruskal-Wallis and Mann-Whitney tests to determine differences between the treatment groups. Results: The results showed that each treatment scored two after a 3-minute exposure to different temperature treatments. The treatment with a temperature of 80°C for 3 minutes (H3T1) showed the best results. Conclusion: It is known that heat increases the fixation rate, but at high temperatures, the fixation rate decreases.